PENGARUH PENALARAN MORAL DAN ORIENTASI NILAI SOSIAL TERHADAP AKUNTABILITAS SOSIAL DAN LINGKUNGAN - Afdal .; Nirwana .; Dinar . (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2014)
Support for social and environmental accountability is lack whereas it is one of the way to solve sosial and environmental problem. The purpose of this study is to investigate the effect of moral reasoning and social value orientation (prosocial, competitive and individualistic) on social and environmental accountability. This paper argues that the higher moral reasoning the higher social and environmental accountability support. Another argument is prosocial support to environmental accountability higher than competitive and individualistic. This study uses survey method with 67 accounting student respondents from 3 universities. The results show that there is significant interraction effect of moral reasoning and social value orientation on social and environmental accontability support.. This finding implications on the education side is that to increase social and environmental support, education must increase moral reasoning and prosocial orientation. On the firm side, to increase social and environmental accountability choose employee who has high moral reasoning and prosocial behavior. Keywords: Social and Environmental Accountability, Moral Reasoning, Social Value Orientation